Workshop on Communicating Climate Information to Farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
As part of efforts to scale up climate services for millions of farmers, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) trained staff from World Vision Tanzania and agricultural extension staff on communicating climate forecast information to farmers that the organizations already serve. The staff training was followed immediately with a 2-day seasonal forecast workshop for a group of 29 farmers, led by six of the trainees. September 2013, Same, Tanzania. Photoa: J.Hansen & A. Tall (CCAFS).